Cervical elongation caused by cervical fibroid mimicking uterine prolapse - Freixo,Marília Lima (2023)
Abstract Growing cervical masses could drag the cervix, predisposing to cervical elongation and prolapse. The differential diagnosis of protrusion of a large vaginal mass includes a uterine or vaginal vault prolapse, a pedunculated uterine leiomyoma or leiomyosarcoma, a uterine stromal tumor or a giant polyp. The authors report a case of an atypical presentation of cervical fibroid with cervical elongation mimicking cervical malignancy.